Looking in a mirror: Asylum in the United States as a reflection of white supremacy. (29th October 2021) - Udani, Adriano; Torres Wedding, Maria
Abstract: Objective: We contend that the asylum process in the United States exhibits how confinement, surveillance, and deportation work together to extend the primary logics of white supremacy: genocide, anti‐blackness, and orientalism. We envision abolition work that uplifts not only asylum seekers but all people with lived experiences of coerced mobility. Methods: Through the lenses of critical race, decolonial theory, and abolition, we conceptualize the asylum process beyond only one violent system that coerces the mobility of migrants. Results: We build a theory that extends scholarly conversations about asylum processes as a system of racial/colonial surveillance, control, and state‐sanctioned violence and that informs abolitionist practices. Conclusion: In order to eradicate all forms of detention, we must build robust strategies that demolish the pillars of white supremacy and rebuild new politics that reject the notion of freedom as a reward to well‐behaved people, resist coerced mobility, foster shared power arrangements in which people with lived experiences of oppression organize to help each other, and reorient a capitalist system that commoditizes and exploits people's oppression. Striving for anything less will lead to more violence.